Assessment of Pharmacogenomic Panel Assay for Prediction of Taxane Toxicities: Preliminary Results - Di Francia, Raffaele; Atripaldi, Luigi; Di Martino, Salvo; Fierro, Carla; Muto, Tommaso; Crispo, Anna; Rossetti, Sabrina; Facchini, Gaetano; Berretta, Massimiliano (Frontiers in Pharmacology, 2017)
Backbone: Paclitaxel and docetaxel are the primary taxane anticancer drugs regularly used to treat, breast, gastric, ovarian, head/neck, and genitourinary neoplasm. Suspension of taxane treatments compromising patient benefits is more frequently caused by peripheral neuropathy and allergy, than to tumor progression. Several strategies for preventing toxicity have been investigated so far. Recently, findings on the genetic variants associated with toxicity and resistance to taxane-based chemotherapy have been reported. Methods. An extensive panel of five polymorphisms on four candidate genes (ABCB1, CYP2C8*3, CYP3A4*1B, XRCC3), previously validated as significant markers related to paclitaxel and Docetaxel toxicity, are analyzed and discussed. We genotyped 76 cancer patients, and 35 of them received paclitaxel or docetaxel-based therapy. What is more, an early outline evaluation of the genotyping costs and benefit was assessed. Results: Out of 35 patients treated with a taxane, six (17,1%) had adverse neuropathy events. Pharmacogenomics analysis showed no correlation between candidate gene polymorphisms and toxicity, except for the XRCC3 AG+GG allele [OR 2.61 (95% CI: 0.91–7.61)] which showed a weak significant trend of risk of neurotoxicities vs the AG allele [OR 1.52 (95% CI: 0.51–4.91)] P= 0.03. Summary: Based on our experimental results and data from the literature, we propose a useful and low-cost genotyping panel assay for the prevention of toxicity in patients undergoing taxane-based therapy. With the individual pharmacogenomics profile, clinicians will have additional information to plan the better treatment for their patients to minimize toxicity and maximize benefits, including determining cost-effectiveness for national healthcare sustainability